PhD competences of food studies - Chelo Gonzalez-Martinez; Cristina L.M. Silva; Rui Costa (International Journal of Food Studies)
In European Higher Education, learning outcomes and competences have been used sometimes with different meanings and sometimes with the same meaning. But both terms have been more commonly used to refer to knowledge, understanding and abilities a student must demonstrate at the end of a learning experience. Their use is a consequence of the paradigm shift of the Bologna Process to a learner centered education environment. The definition of standards of competences (or learning outcomes) for the PhD degree is thus a need for the quality assurance of this degree. In this work, subject-specific and generic competences for the PhD in Food Science and Technology and their alignment with the European Qualifications Framework (EQF) level descriptors for quality assurance purposes have been identified.